Unraveling the performance of dispersion-corrected functionals for the accurate description of weakly bound natural polyphenols - Di Meo, Florent; Bayach, Imene; Trouillas, Patrick; Sancho-García, Juan-Carlos (Journal of molecular modeling, 2015)
Long-range non-covalent interactions play a key role in the chemistry of natural polyphenols. We have previously proposed a description of supramolecular polyphenol complexes by the B3P86 density functional coupled with some corrections for dispersion. We couple here the B3P86 functional with the D3 correction for dispersion, assessing systematically the accuracy of the new B3P86-D3 model using for that the well-known S66, HB23, NCCE31, and S12L datasets for non-covalent interactions. Furthermore, the association energies of these complexes were carefully compared to those obtained by other dispersion-corrected functionals, such as B(3)LYP-D3, BP86-D3 or B3P86-NL. Finally, this set of models were also applied to a database composed of seven non-covalent polyphenol complexes of the most interest. Graphical abstract Weakly bound natural polyphenolsᅟ.
Keywords: polyfenoly; Molecular Structure; Models, Molecular; chemické databáze; Polyphenols; molekulární modely; Databases, Chemical; molekulární struktura